Pemberian Propolis terhadap Mempercepat Penyembuhan Luka Perineum pada Ibu Postpartum - Gangsar Indah Lestari; Muhamad Ridwan; Firda Fibrila (Jurnal Kesehatan Metro Sai Wawai, 2020)
Background: The management of the perineum wound is not good to cause infections that affect the prolonged healing of perineum wounds. Purpose: Research aims to determine the effect of giving propolis on the length of healing of perineum wounds in postpartum mothers. Method: This study used a quasi-experimental design. The subject of the study was the postpartum mother who suffered perineum wounds. Sample cases as much as 39 and control samples as much as 39, the total samples of 79 postpartum mothers. Samples taken in the Non-Random sample in the form of Accidental sampling initiated a sample group of cases then sample control group according to criteria of inclusion and exclusion of research. Data analysis using T-Test (Paired T-Test). Result: Research shows the average degree of wound perineum in mothers group given propolis of 1.82 whereas in mothers who are not given propolis of 1.85. The average length of wound healing of perineum in mothers group given Propolis is 3.38 day while on a mother who is not given propolis of 1.85 and obtained p-value = 0.000 (≤ alpha 0.05). Conclusion: Perineum wound in postpartum mothers given propolis will be healed faster than those who are not given propolis. Midwives while giving care to the mother postpartum with perineum wounds can utilize propolis to accelerate the healing process while observing nutrition, personal hygiene, and consider the economic and ethical aspects.Latar belakang: Penatalaksanaan luka perineum tidak baik menyebakan infeksi yang berpengaruh terhadap lama penyembuhan luka perineum. Tujuan: Penelitian bertujuan mengetahui pengaruh pemberian propolis terhadap lama penyembuhan luka perineum pada ibu postpartum. Metode: Penelitian menggunakan rancangan quasi eksperimen. Subyek penelitian adalah ibu post partum yang mengalami luka perineum. Sampel kasus sebanyak 39 dan sampel kontrol sebanyak 39, total sampel 79 ibu postpartum. Sampel diambil secara non random sample berupa acidental sampling dimulai sampel kelompok kasus lalu sampel kelompok kontrol sesuai kriteria inklusi dan eksklusi penelitian. Analisis data mengunakan T-test (paired t-test). Hasil: Penelitian menunjukkan rata-rata derajat luka perineum pada kelompok ibu yang diberi propolis sebesar 1,82 sedangkan pada ibu yang tidak diberi propolis sebesar 1,85. Rata-rata lama penyembuhan luka perineum pada kelompok ibu yang diberi propolis adalah 3,38 hari sedangkan pada ibu yang tidak diberi propolis sebesar 1,85 dan didapatkan p value = 0,000 (≤ alpha 0,05). Simpulan: Luka perineum pada ibu postpartum yang diberi propolis akan lebih cepat sembuh dibanding dengan yang tidak diberi propolis. Bidan saat memberikan asuhan pada ibu post partum dengan luka perineum bisa memanfaatkan propolis guna mempercepat proses penyembuhan dengan tetap memperhatikan  nutrisi, personal hygiene dan mempertimbangkan aspek ekonomis dan etika.